Growth response of eight tropical turfgrass species to salinity - Uddin, Md. Kamal; Juraimi, Abdul Shukor; Ismail, Mohd Razi; Othman, Radziah; Abd Rahim, Anuar (Academic Journals, 2009)
Irrigation seawater of different salinity levels (0, 24, 48 and 72 dSm-1) were applied to experimental plants grown in a plastic pots filled with a mixture of sand and peat (9:1). The results were analyzed using SAS and treatment means were compared using LSD Test. The results indicated that Paspalum vaginatum (seashore paspalum) (SP), Zoysia matrella (manilagrass) (MG), Pasplaum vaginatum local (SPL), Cynodon dactylon (common bermuda) (CB), Cynodon dactylon (bermuda greenless park) (GLP), Eremochloa ophiuroides (centipede) (CP), Axonopus compressus (cow grass) (CG) and Axonopus affinis (narrowleaf carpet grass) (NCG) experienced a 50% shoot growth reduction at the EC of 39.8, 36.5, 26.1, 25.9, 21.7, 22.4, 17.0 and 18.3 dSm-1, respectively, and a 50% root growth reduction at the EC of 49.4, 42.1, 29.9, 29.7, 26.0 24.8, 18.8 and 20.0 dSm-1, respectively. The ranking for salinity tolerance of selected grasses was SP>MG>SPL>CB>GLP>CP>NCG>CG. The results indicate the importance of the selection of turfgrass varieties according to the soil salinity and seawater salinity levels to be used for irrigation.